Performance analysis of a small-scale Orthopter-type Vertical Axis Wind Turbine. Issue 180 (September 2018) - ElCheikh, A.; Elkhoury, M.; Kiwata, T.; Kono, T.
Abstract: Orthopter-type Vertical Axis Wind Turbines (O-VAWT) are energy capturing devices which are suitable for micro-generation in urban areas. This paper aims to study the effect of number of blades (solidity), Aspect Ratio (AR), and wind speed on the performance of a small-scale O-VAWT using experimental and numerical techniques. Wind tunnel experiments were carried out to measure the torque of two-, three, and four-bladed turbine, each at a set of different wind speeds and blade aspect ratios. Increasing solidity was achieved by either decreasing the blade aspect ratio or increasing the number of blades, both resulting in a higher peak power coefficient (Cp, max ) of the VAWT. The startup characteristics of the O-VAWT were also examined at different aspect ratios, and showed its capability to start-up even at low wind speeds. In addition, numerical simulations were carried out using an unsteady three-dimensional Delayed Detached Eddy Simulation (DDES) with Spalart Allmaras model. Numerical results of power coefficient were validated by comparison against available experimental data. Moreover, velocity and vorticity contours for the two-, three-, and four-bladed turbines, and pressure contours at different span-wise locations were thoroughly analyzed to link the flow field aerodynamics to relevant changes in power coefficient for different rotor solidities. Highlights: The effect of solidity on the performance of an Orthopter-type vertical axis wind turbine is experimentally investigated. A CFD approach is employed to analyze the 3D flow structures around turbines of different solidities. The maximum power coefficient attained by the turbine increases with solidity. Adding more blades results in attaining the maximum power coefficient at lower tip speed ratios.